PEMENUHAN NUTRISI (THE FULFILLMENT OF NUTRITION): LITERATUR REVIEW - Putu Eka Nopitasari; Mochamad Heri (Jurnal Online Keperawatan Indonesia, 2021)
Background: The need for nutritional fulfillment is a need that must be met to maintain a healthy body. Given the benefits of nutrition and fluids in the body can help the process of growth and development and prevent various diseases due to lack of nutrition. Nutrition is one of the main basic human needs needed for life. Failure to fulfill nutritional needs will result in nutritional disturbances which will have an impact on growth and development disorders. Purpose: The purpose of this literature review is to identify and analyze journals related to the topic / title of discussion, namely to explain the fulfillment of nutritional needs. Methods: This study used a literature review method with the database used, namely Google Scholar, and PubMed were taken to filter out relevant articles. The initial term for screening related studies was " fulfillment of nutritional needs". Articles are limited based on inclusion and exclusion criteria published at least in the last 3 years. Result: The discussion in this study can help readers and nurses in understanding the fulfillment of nutritional needs.